MOTS-c: A promising mitochondrial-derived peptide for therapeutic exploitation - Zheng, Yuejun; Wei, Zilin; Wang, Tianhui (Frontiers in Endocrinology, 2023)
Mitochondrial ORF of the 12S rRNA Type-C (MOTS-c) is a mitochondrial-derived peptide composed of 16 amino acids encoded by the 12SrRNA region of the mitochondrial genome. The MOTS-c protein is transferred to the nucleus during metabolic stress and directs the expression of nuclear genes to promote cell balance. Different tissues co-expressed the protein with mitochondria, and plasma also contained the protein, but its level decreased with age. In addition, MOTS-c has been shown to improve glucose metabolism in skeletal muscle, which indicates its benefits for diseases such as diabetes, obesity, and aging. Nevertheless, MOTS-c has been used less frequently in disease treatment, and no effective method of applying MOTS-c in the clinic has been developed. Throughout this paper, we discussed the discovery and physiological function of mitochondrial-derived polypeptide MOTS-c, and the application of MOTS-c in the treatment of various diseases, such as aging, cardiovascular disease, insulin resistance, and inflammation. To provide additional ideas for future research and development, we tapped into the molecular mechanisms and therapeutic potentials of MOTS-c to improve diseases and combined the technology with synthetic biology in order to offer a new approach to its development and application.